1986
DOI: 10.1039/c39860001611
|View full text |Cite
|
Sign up to set email alerts
|

In situ Fourier transform i.r. observation of methylating species in ZSM-5

Abstract: In situ Fourier transform i.r. spectra show that MeOH in ZSM-5 forms an AlOMe species above 473 K which correlates with the onset of hydrocarbon formation and which methylates benzene, ethene, propene, and cyclopentene; MeOMe is protonated by internal acid sites at l o w temperatures but forms the same methylating species at 473 K and above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 0 publications
1
36
1
Order By: Relevance
“…14(e), while the methyl stretch, deformation and rock are at similar positions to those in HY, the methanol O-H stretch and deformation modes have vanished. These observations suggest that complete conversion of methanol to framework methoxy has occurred, which is remarkable, as methanol was introduced at 298 K; thus methoxylation of the Brønsted acid sites, the first step in the MTH process, has occurred at room temperature contrary to studies using more conventional spectroscopy techniques [66][67][68] and modelling studies [69][70][71][72] which suggest a significant energy barrier to the process. INS spectroscopy has also been used to investigate the working catalyst.…”
contrasting
confidence: 40%
“…14(e), while the methyl stretch, deformation and rock are at similar positions to those in HY, the methanol O-H stretch and deformation modes have vanished. These observations suggest that complete conversion of methanol to framework methoxy has occurred, which is remarkable, as methanol was introduced at 298 K; thus methoxylation of the Brønsted acid sites, the first step in the MTH process, has occurred at room temperature contrary to studies using more conventional spectroscopy techniques [66][67][68] and modelling studies [69][70][71][72] which suggest a significant energy barrier to the process. INS spectroscopy has also been used to investigate the working catalyst.…”
contrasting
confidence: 40%
“…Several spectroscopic investigations have shown that methoxy groups may indeed be formed on various sites on zeolite surfaces from methanol at moderate temperatures and that these, in turn, may react with aromatics or other unsaturated species to yield methylation products in apparent agreement with a stepwise mechanism [11][12][13][14][15]. Experimental kinetic data, on the other hand, are more easily reconcilable with the direct reaction mechanism not involving an intermediate [16][17][18].…”
Section: Introductionmentioning
confidence: 80%
“…Upon the introduction of benzene the methoxy bands were reduced, which is an indication of methylation. Also employing a setup where reactants were sequentially dosed, Howe and co-workers [39,42] were able to show that methoxy groups could methylate alkenes such as ethene and cyclopentene in addition to benzene. The importance of methoxy groups on Brønsted sites compared to methoxy groups on silanols was emphasized [42].…”
Section: Insights From Spectroscopic Studiesmentioning
confidence: 98%
“…Also employing a setup where reactants were sequentially dosed, Howe and co-workers [39,42] were able to show that methoxy groups could methylate alkenes such as ethene and cyclopentene in addition to benzene. The importance of methoxy groups on Brønsted sites compared to methoxy groups on silanols was emphasized [42]. Further, Datka et al [41] studied not only the reaction of methanol followed by admission of benzene to the FTIR cell, but also admitted the two reactants simultaneously.…”
Section: Insights From Spectroscopic Studiesmentioning
confidence: 98%
See 1 more Smart Citation